STUDENTS' LEARNING DIFFICULTIES IN SECONDARY SCHOOL SCIENCES LEARNING DURING THE IMPLEMENTATION OF MERDEKA CURRICULUM IN INDONESIA - Fermunesti, Rasta; Sari, Monica Prima; Arif, Khairil; Putri, Azza Nuzullah; Lestari, Tuti (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2026)
Learning difficulties arise when students are unable to learn effectively due to various threats, obstacles, and disturbances. The introduction of the Emancipated Curriculum (Kurikulum Merdeka) as Indonesia's new national education curriculum has highlighted several barriers and challenges. From the students' perspectives, this new curriculum presents additional challenges in the already demanding subject of science. This study aims to explore the learning difficulties faced by students at the secondary school level and the factors contributing to these challenges. Conducted in two secondary schools in Padang City designated as Sekolah Penggerak since 2021, this descriptive study gathered data on students' learning difficulties through a Likert-scale questionnaire, which was then analyzed using descriptive statistics. The findings revealed that factors contributing to students' learning difficulties in science include talent, cognitive ability, study habits, comprehension of learning objectives, teaching methods employed by instructors, the school's social environment, and the condition of school facilities. These insights can provide valuable information to school leaders and stakeholders for better implementation of the Emancipated Curriculum.